Legal Analysis of Content Monetization by Influencers without Disclosure as A Violation of Consumer Protection Law - Fachry Satrio Pringgowidigdo; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2026)
The development of digital technology has driven a transformation in marketing practices through social media, giving rise to the phenomenon of influencer marketing as an effective promotional strategy. Influencers not only act as messengers but also function as economic actors who profit by monetizing content through endorsement activities. Problems arise when monetized content is not accompanied by disclosure regarding commercial relationships, thus potentially misleading consumers and violating the principle of transparency from the perspective of consumer protection law. This study is directed at analyzing the practice of content monetization without disclosure, identifying the forms of legal violations that occur, and examining the legal responsibilities of influencers from the civil, criminal, administrative, and ethical perspectives. The method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that this practice can be qualified as misleading advertising because it creates an imbalance of information between business actors, influencers, and consumers. In addition, influencers can be held legally accountable if the content they convey causes harm. This study concludes that influencers are part of digital advertising actors who are obliged to convey information transparently. Therefore, strengthening regulations related to disclosure obligations is needed to create effective and equitable consumer protection in the digital era.